IMPROVEMENT OF GRADE 1 STUDENTS’ ABILITY OF SMK NEGERI 1 WATUBANGGA IN SPEAKING THROUGH MIND MAPPING STRATEGIES - Wayan Pageyasa (Universitas Sembilanbelas November Kolaka, 2016)
Low ability of students in grade 1 SMK Negeri 1 Watubangga in speaking due to less effective and interestingly learning to speak are implemented. Therefore, it applied a creative strategy to solve problems of practical learning to speak it. The strategy is